Orthodontic correction of acquired open bite with TMJ degeneration: A retrospective study of outcomes and stability - Li-Fan Hsu; Yi-Jen Liu; Shin-Huei Wang; Yunn-Jy Chen; Yi-Jane Chen; Chung-Chen Jane Yao (Journal of the Formosan Medical Association, 2024)
Background/Purpose: Newly developed temporary anchorage devices (TADs) serve a strong orthodontic anchorage to intrude molars for correction of anterior open bite (AOB). We measured cephalometric changes in skeletal open bite patients which developed subsequently to temporomandibular joint disorders with bilateral point contacts at terminal molars. Methods: We retrospectively recruited 32 patients who had been treated their TMD before orthodontic correction (overbite: −3.14 ± 1.86 mm). Partial orthodontic appliances were used to intrude posterior teeth using TADs until positive OB obtained (T1). Full fixed appliances were then used to achieve proper overjet and overbite (T2). We collected lateral cephalograms before (T0), during (T1) and after (T2) treatment, and at follow-ups (T3). Using ANOVA, we analyzed the differences among these time points to determine treatment changes and stability of orthodontic results. Results: In this group predominantly comprising young adult women, orthodontic treatment with TADs significantly reduced upper posterior dental heights (T2-T0:-1.84 ± 0.66 mm) and facilitated the retraction and uprighting upper incisors (T2-T0: −9.92 ± 1.72°), to achieve appropriate OJ (T2-T0: −3.21 ± 0.49 mm) and OB (T2-T0: 4.10 ± 0.28 mm) with p < 0.05. Except upper posterior dental height, most of cephalometric changes including OJ, OB, and upper incisal axis remained significant at follow-ups with retention time of 3.7 ± 2.6 years. Only three out of 30 patients experienced small amount of open bite at T3. Conclusion: Orthodontic correction of OJ remained relatively stable among 90 % of patients with TMJ degeneration by intrusion via TADs. This modern but conservative orthodontic approach can improve occlusal functions in skeletal open bites.